Kedudukan Hukum Lembaga Pengelola Investasi dengan Kewenangan Khusus (Sui Generis) di Indonesia - Dhea Putri Wulandari (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The Investment Management Institution (LPI) was established based on the mandate of the Job Creation Law in Chapter X concerning Central Government Investment and the facilitation of National Strategic Projects in Article 154 paragraph (3) which states that Central Government Investment can be implemented by the Minister of Finance as the State Treasurer or an institution given special authority (sui generis). In the field of taxation, there is special treatment in terms of transactions involving the Investment Management Institution (LPI) including transactions both directly and indirectly with the entities it owns. In terms of bankruptcy, the Investment Management Institution (LPI) is treated specially and cannot be declared bankrupt unless it can be proven to be insolvent. And the nature and norms or rules set by the Investment Management Institution or LPI only apply specifically to parties who cooperate or make business agreements with the Investment Management Institution (LPI) and do not apply generally to everyone, so that its nature is a consensus between the parties.